Data collection using miniature aerial vehicles in wireless sensor networks. (1st February 2016) - Mathur, Prateek; Nielsen, Rasmus H.; Prasad, Neeli R.; Prasad, Ramjee
Abstract : Energy constraints of sensor nodes in wireless sensor networks (WSNs) is a major challenge and minimising the overall data transmitted across a network using data aggregation, distributed source coding, and compressive sensing have been proposed as mechanisms for energy saving. Similarly, use of mobile nodes capable of relocating within the network has been widely explored for energy saving. In this study, the authors propose a novel method for using miniature aerial vehicles for data collection instead of actively sensing from a deployed network. The proposed mechanism is referred as data collection fly ( DCFly ). It is suitable for data collection from WSNs deployed in harsh‐undulating terrain with the base station located far from the sensing region. The DCFly is compared with data collection based on multi‐hop data aggregation and data collection with mobile sinks. The numerical results justify that the proposed data collection mechanism is effective and efficient for use in WSNs.